Mechanisms of plasticity in a Caenorhabditis elegans mechanosensory circuit - Bozorgmehr, Tahereh; Ardiel, Evan L.; McEwan, Andrea H.; Rankin, Catharine H. (Frontiers in Physiology, 2013)
Despite having a small nervous system (302 neurons) and relatively short lifespan (14-21 days), the nematode Caenorhabditis elegans has a substantial ability to change its behavior in response to experience. The behaviour discussed here is the tap withdrawal response, whereby the worm crawls backwards a brief distance in response to a non-localized stimulus to the side of the Petri plate within which it lives. The neural circuit that underlies this behaviour is primarily made up of 5 sensory neurons and four pairs of interneurons. In this review we describe two classes of mechanosensory plasticity: adult learning and memory and experience dependent changes during development. As worms develop through young adult and adult stages there is a shift towards deeper habituation of response probability that is likely the result of changes in sensitivity to stimulus intensity. Adult worms show short- intermediate- and long-term habituation as well as context dependent habituation. Short-term habituation requires glutamate signalling and auto-phosphorylation of voltage-dependent potassium channels and is modulated by dopamine signalling in the mechanosensory neurons. Long-term memory for habituation is mediated by down-regulation of expression of an AMPA-type glutamate receptor subunit. Intermediate memory involves an increase in release of an inhibitory neuropeptide. Depriving larval worms of mechanosensory stimulation early in development leads to fewer synaptic vesicles in the mechanosensory neurons and lower levels of an AMPA-type glutamate receptor subunit in the interneurons. Overall, the mechanosensory system of C. elegans shows a great deal of experience dependent plasticity both during development and as an adult. The simplest form of learning, habituation, is not so simple and is mediated and/or modulated by a number of different processes, some of which we are beginning to understand.